Ralgro-implanted bulls: Performance, carcass characteristics, longissimus palatability and carcass electrical stimulation - Greathouse, J.R.; Hunt, Melvin C.; Dikeman, Michael E.; Corah, L.R.; Kastner, Curtis L.; Kropf, Donald H. (American Society of Animal Science, 2008)
Twenty of 40 Angus bulls were implanted (I) five times with 36 mg of Ralgro| at average intervals of 106 d, beginning near birth. All bulls and their dams were on bluestem pasture initially and, at an average age of 320 d bulls were fed a concentrate diet until they were slaughtered, weighing either 454 or 499 kg. One side of each carcass was electrically stimulated. Average daily gain and feed efficiency of I bulls improved 6.5 to 10.4% and 7.9 to 8.1%, respectively, depending upon the end point comparison with nonimplanted (NI) bulls. Implanted bulls attained their slaughter weights 42 d sooner than did NI bulls. Implantation decreased (P<.05) penis weight and length, testicle weight, volume and density, but did not affect (P>.05) seminal vesicle and pituitary weights. Carcasses from I bulls had more (P<.05) skeletal ossification and were fatter than carcasses from NI bulls. Marbling scores, quality grades and longissimus cooking losses and juiciness scores were not affected (P>.05) by implantation. Taste panel flavor intensity and detectable connective tissue scores were higher (P<.05) for steaks from I bulls than from NI bulls. Longissimus steak tenderness evaluations were higher (P<.05) for both I slaughter groups than for the NI light-weight group and were higher (P<.05) for the I lightweight group than for the NI heavy-weight group. Longissimus tenderness tended (P = .11) to be higher for steaks from the I heavy-weight group than those from the NI heavy-weight group. Electrical stimulation produced (P<.05) a softer, coarser textured lean, but it did not affect lean color, marbling or quality grade. Steaks from electrically stimulated sides tended to have higher (P = .09) myofibrillar tenderness scores and lower (P = .06) flavor scores than steaks from nonstimulated sides.
Keywords: Food science; Bulls; Ralgro implantation; Performance; Electrical stimulation; Palatability; Zeranol